Peran Patroli Ops Aman Nusa dalam Menurunkan Presentase Covid-19 di Wilayah Hukum Polres Manokwari - Herman Agustinus Marini (Advances in Police Science Research Journal, 2021)
This research was motivated by the level of the spread of Covid-19 that occurred in Manokwari and the lack of public awareness in adhering to the Health protocol. The level of the spread of the covid-19 virus in the city of Manokwari in recent months has been quite significant. This is due to the fact that the community feels trivial and does not comply with the Health protocol of the virus so that the level of its spread has increased so that the need for participation from the Police to help prevent the spread of Covid-19 in the city of Manokwari, the condition of Kamtimbaspun is disturbed. So that indirectly this can also disrupt the wheels of the economy in Manokwari City. Because of this, a study was conducted with the aim of finding out how the Safe Ops of Nusa Polres Manokwari could take preventive or repressive actions through routine patrols. The research was conducted with a qualitative approach, analytical descriptive research methods, and data collection techniques through in-depth interviews, observation and document study. The results of the research analyzed using Role Theory, Routine Activity Theory, and Management Theory along with the patrol concept (Perkabaharkam number 1 of 2017) shows a conclusion that the implementation of patrols is quite good with the efforts that have been made but there are still some deficiencies in the implementation of patrols. This can be proven by the implementation of duties from the Aman Ops in Nusa Tenggara, such as swiping masks and counseling about Covid-19 in the city of Manokwari being able to dominate and ingratiate people to work together in breaking the chain of the spread of Covid-19. In addition, there are still findings of problems in each patrol implementation, including the lack of the number of patrol personnel, the absence of policewomen on the patrol team and the lack of strict sanctions and punishments for violators of the Covid-19 Health Protocol. Based on the results of the research, the authors provide advice to Sat Ops Aman Nusa, namely giving strict sanctions and punishments for violators of the Covid-19 Health protocol by providing fines and penalties for children under and over 17 years, increasing the number of patrol personnel, involving policewomen in carrying out patrol activities. renewal of patrol facilities and infrastructure, both two-wheeled and four-wheeled vehicles and the provision of other sarpras.